Instant messaging reference : a practical guide - Bridgewater, Rachel; Cole, Meryl B.; ScienceDirect eBooks (Witney : Chandos Publishing (Oxford) Ltd, 2009)
Virtual reference is a vital component in twenty-first century reference service and the time for debate over its virtues and necessity has passed. This book focuses on the practical implementation of instant messaging (IM), including privacy and security and its future potential.
Introduction -- Virtual reference: an overview and brief history -- IM Basics -- Basic IM reference -- Set-up and use -- Conducting the IM reference interview -- Managing patron expectations and staff attitudes -- Evaluating/updating service -- Taking your service to the next level: widgets, enterprise IM and collaborative IM -- Issues with IM reference -- Promoting your IM reference service.
Includes bibliographical references (pages 201-206) and index.
Elsevier
Keywords: Instant messaging; Electronic reference services (Libraries); Libraries and the Internet; Social media; LANGUAGE ARTS & DISCIPLINES -- Library & Information Science -- General; Electronic reference services (Libraries); Instant messaging; Libraries and the Internet; Social media; Electronic books